Environmental dimorphism of the incidence of significant correlations between feet and body trunk parameters among 4-6-year-old children - Mirosław Mrozkowiak (Kazimierz Wielki University, 2018)
Introduction. The issue of sexual and environmental dimorphism within the scope of somatic characteristics is discussed in numerous publications. Sexual dimorphism is obvious, well-described and undisputed. There are relatively few publications concerning statodynamic correlations between the parameters of feet and hip zone. Material and method. The study conducted with the group of children aged 4 to 6 years enabled to record 2,988 observations including 1,551 in the urban environment and 1,437 in the rural environment with regard to the measurement of the 87 parameters describing trunk and feet. The station for measurement of the selected parameters using the photogrammetric method consisted of a computer, a card, software, a display monitor, a printer and a projection-reception device with a camera. Conclusions 1. The number of foot parameters revealing significant correlations with trunk parameters and differentiating both environments is the same. Yet, in the rural environment the correlation with trunk parameters is slightly higher. The parameters differentiating the rural environment are the features describing the longitudinal arch and the ones relating to the urban environment are describing the morphological characteristics and disorders of the toe position. 2. The number of trunk parameters with which the foot parameters significantly correlate is considerably higher in the individuals from the urban environment and this correlation is more common. The number of sagittal parameters is the biggest, followed by the number of frontal parameters and the smallest number of transverse parameters.